Yoga Training for Stress Reduction in Pregnant Teenagers - แก้วเมืองฝาง, รุจา; ปรารมย์, สุภาพร; วิหคหาญ, พัชรินทร์; สุภารี, นิธิมา (Princess of Naradhiwas University Journal, 2019)
The majority of teenage pregnancies are unplanned pregnancies with insufficient social support. This means pregnant teenagers are not ready to face both physical and psychological changes. They are often confused, afraid, worried, and stressful. Since stress affects pregnant teenagers and their babies, there are many different ways to relieve stress. One of the most effective ways to relieve stress is Yoga training with breath control following 8 stages of Ashtanga yoga. Practicing Ashtanga yoga for 30-40 minutes, 3 times a week, can control stress effecting on pregnant teenagers. The consequences of regular Ashtanga yoga practice of pregnant teenagers are more peaceful, relaxed, and focused. And finally their stress is relieved.